1,1,3,3-Tetraisopropyldisiloxane-1,3-diyl (TIPS) migration facilitates one-pot formation of enantiomerically pure methyl 2,3-epoxy-D-xylonate - Wang, Y; Fleet, G; Zhao, L (1998)
The reaction of 3,5-O-(1,1,3,3-tetraisopropyldisiloxane-1,3-diyl)-2-O- trifluoromethanesulfonyl-D-lyxono-1,4-lactone with K2CO3 in dry methanol at -10°C gave enantiomerically pure methyl 2,3-anhydro-4,5-O-(1,1,3,3- tetraisopropyldisiloxane-1,3-diyl)-D-xylonate as the single product, resulting from migration of the TIPS group in an alkoxide intermediate.